2023
DOI: 10.3389/fpsyg.2022.1059486
|View full text |Cite
|
Sign up to set email alerts
|

School victimization and Internet addiction among Chinese adolescents: The mediating roles of life satisfaction and loneliness

Abstract: The present study investigated the possibility of life satisfaction and loneliness mediating the link between school victimization and Internet addiction. A total of 3,363 middle/high school students (45% males; Mage = 15.67 years old, SD = 1.58) completed a series of self-report questionnaires, which included school victimization, life satisfaction, loneliness, and Internet addiction. The findings demonstrated a positive relationship between school victimization and Internet addiction. In addition, life satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…According to the results of a survey of 582 Chinese college students by Yanhong Zhang et al, Loneliness was significantly and positively associated with mobile phone addiction [ 23 ]. In addition, studies have shown that lonely and depressed individuals prefer online social interaction over face-to-face communication, leading to increased Internet use or compulsive Internet use in adolescents, increasing the incidence of IA in adolescents [ 24 ]. Therefore, this study proposes hypothesis 2 that loneliness mediates between social anxiety and IA.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of a survey of 582 Chinese college students by Yanhong Zhang et al, Loneliness was significantly and positively associated with mobile phone addiction [ 23 ]. In addition, studies have shown that lonely and depressed individuals prefer online social interaction over face-to-face communication, leading to increased Internet use or compulsive Internet use in adolescents, increasing the incidence of IA in adolescents [ 24 ]. Therefore, this study proposes hypothesis 2 that loneliness mediates between social anxiety and IA.…”
Section: Introductionmentioning
confidence: 99%
“…The way parents educate their children can significantly predict their life satisfaction [ 18 ]. Moreover, life satisfaction has been frequently investigated as a mediating factor [ 19 ]. Therefore, this study suggests that life satisfaction may mediate between the family parenting style and internet addiction among college students.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, life satisfaction has been frequently investigated as a mediating element [ 19 , 52 , 53 ]. A study examining the mediating mechanism of life satisfaction between bullying at school and internet addiction [ 19 ] found that adolescents who were bullied at school developed negative perceptions and evaluations of themselves and others because of their victimization experiences. Bullied teenagers are more inclined to extend their lives online and possibly develop internet addiction because of a lack of realistic communication in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…GST focuses on the role of strain or stress in individuals’ lives, positing that strain arises when individuals perceive a disjunction between their desired goals and their ability to achieve them, or when they experience the removal of positively valued stimuli ( Agnew and White, 1992 ). Over time, GST has been applied to understand a range of deviant behaviors, including alcohol abuse ( Swatt et al, 2007 ), excessive drug use ( Zweig et al, 2015 ) and problematic internet use among adolescents ( Shi and Wang, 2023 ). Moreover, the GST framework has been utilized to investigate the association between offline bully-victimization and cyberbullying behavior ( Jang et al, 2014 ), as well as between relational victimization and video game addiction among young individuals ( Niu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%